2018
DOI: 10.1111/hdi.12653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high amylose resistant starch (HAM‐RS2) supplementation on biomarkers of inflammation and oxidative stress in hemodialysis patients: a randomized clinical trial

Abstract: Administration of HAM-RS2 for eight weeks significantly reduced levels of inflammatory and oxidative markers in hemodialysis patients confirming the results observed in CKD animals. Long term trials are needed to explore the impact of HAM-RS2 supplementation on clinical outcomes in end stage renal disease population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 44 publications
2
57
1
Order By: Relevance
“…As shown in our previous study, HAM-RS2-treated patients exhibited a significant reduction in serum concentrations in blood urea nitrogen (BUN). 9 Similarly, in a recent study, Sirich et al found a reduction of urea levels in their ESRD patients supplemented with amylose for 6 weeks. 13 The reduction in urea level with amylose supplementation may, in part, be due to SCFAs' trapping of ammonia, which was derived from hydrolysis of urea by urease-possessing colonic bacteria.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…As shown in our previous study, HAM-RS2-treated patients exhibited a significant reduction in serum concentrations in blood urea nitrogen (BUN). 9 Similarly, in a recent study, Sirich et al found a reduction of urea levels in their ESRD patients supplemented with amylose for 6 weeks. 13 The reduction in urea level with amylose supplementation may, in part, be due to SCFAs' trapping of ammonia, which was derived from hydrolysis of urea by urease-possessing colonic bacteria.…”
Section: Discussionmentioning
confidence: 81%
“…As shown in our previous study, HAM‐RS2‐treated patients exhibited a significant reduction in serum concentrations in blood urea nitrogen (BUN) . Similarly, in a recent study, Sirich et al found a reduction of urea levels in their ESRD patients supplemented with amylose for 6 weeks .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two researchers (MR and MV) independently evaluated the articles in the second screening stage and 185 studies that were not relevant were eliminated. Finally 13 studies with 14 effect sizes met the inclusion criteria and were included in the final analysis [17,18,20,[26][27][28][29][30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the effect of resistant starch on inflammatory markers are conflicting. Some studies showed a significant decrease in inflammatory markers after RS consumption compared to placebo [17,18], but the results of some other studies were inconsistent [19,20].…”
mentioning
confidence: 99%